The genetic basis of a social polymorphism in halictid bees. Issue 1 (December 2018) - Kocher, Sarah; Mallarino, Ricardo; Rubin, Benjamin; Yu, Douglas; Hoekstra, Hopi; Pierce, Naomi
Abstract The emergence of eusociality represents a major evolutionary transition from solitary to group reproduction. The most commonly studied eusocial species, honey bees and ants, represent the behavioral extremes of social evolution but lack close relatives that are non-social. Unlike these species, the halictid beeLasioglossum albipes produces both solitary and eusocial nests and this intraspecific variation has a genetic basis. Here, we identify genetic variants associated with this polymorphism, including one located in the intron ofsyntaxin 1a (syx1a), a gene that mediates synaptic vesicle release. We show that this variant can alter gene expression in a pattern consistent with differences between social and solitary bees. Surprisingly, syx1a and several other genes associated with sociality inL .albipes have also been implicated in autism spectrum disorder in humans. Thus, genes underlying behavioral variation inL .albipes may also shape social behaviors across a wide range of taxa, including humans. The halictid beeLasioglossum albipes has both solitary and eusocial individuals, making it a model for social evolution. Here, Kocher et al. identify a genetic variation associated with this social polymorphism, including a variant that can regulate the expression of an autism-associated gene, syntaxin 1a .